Comparison of Correlated Comorbidities in Male and Female Sexual Dysfunction: Findings From the Third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). Issue 5 (6th April 2018) - Polland, Allison; Davis, Meghan; Zeymo, Alexander; Venkatesan, Krishnan
Abstract: Background: Many of the same mechanisms involved in the sexual arousal-response system in men exist in women and can be affected by underlying general medical conditions. Aim: To assess whether sexual function in men and women is correlated with similar comorbidities. Methods: This study was a secondary analysis of the 3rd National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a prospective stratified probability sample of British individuals 16 to 74 years old interviewed from 2010 to 2012. We assessed for an association between sexual function and the following comorbidities: heart attack, heart disease, hypertension, stroke, diabetes, chronic lung disease, depression, other mental health conditions, other neurologic conditions, obesity, menopause, incontinence, smoking status, and age. Outcome: An association was found between multiple medical comorbidities and sexual dysfunction in women and in men. Results: 6, 711 women and 4, 872 men responded to the survey, were in a relationship, and reported sexual activity in the past year. The average age of the women was 35.4 ± 14.1 and that of the men was 36.8 ± 15.6. There was an association between sexual function and all variables assessed except for chronic lung disease, heart attack, and incontinence in women compared with stroke, other neurologic conditions, incontinence,  and smoking status in men. Comorbidities associated with erectile dysfunction included depression, diabetes, and other heart disease, whereas comorbidities associated with difficulty with lubrication included depression and other heart disease. Menopause was predictive of sexual dysfunction. Male sexual function appeared to decline after 45.5 years of age. Clinical Implications: Physicians should be aware of the correlation between medical comorbidities and sexual dysfunction in women and men and should ask patients about specific symptoms that might be associated with underlying medical conditions. Strengths and Limitations: Use of a stratified probability sample compared with a convenience sample results in capturing of associations representative of the population. Inclusion of multiple comorbidities in the multivariate analysis allows us to understand the effects of several variables on sexual function. Although this study shows only an association, further research could determine whether there is a causal relation between comorbidities and sexual dysfunction in women. Conclusion: Multiple medical comorbidities are associated with sexual dysfunction not only in men but also in women.